Exploring Fluid Mechanics Concepts in the Local Wisdom of Pacu Jalur as a Context for Learning Fluid Mechanics - Achmad Lutfi Adriansyah; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Pacu Jalur is a cultural tradition of the Kuantan Singingi community that embodies various physics concepts, particularly those related to fluid mechanics. This study aims to explore the concepts of fluid statics and fluid dynamics embedded in the Pacu Jalur tradition as a context for ethnoscience-based physics learning. A descriptive qualitative approach was employed through a literature review and documentation study. Data were collected from scientific articles, books, photographic and video documentation, and official sources related to the history and implementation of Pacu Jalur. The data were analyzed by identifying Pacu Jalur phenomena, classifying them into fluid statics and fluid dynamics, interpreting their relationships with established physics principles, and examining their potential integration into physics learning. The findings reveal four fluid mechanics concepts associated with the Pacu Jalur tradition: hydrostatic pressure, Archimedes' principle, the continuity principle, and Bernoulli's principle. These concepts are reflected in the submerged portion and floating behavior of the Jalur boat, the interaction between its bow and the surrounding water flow, and its long and slender hull geometry. The findings suggest that Pacu Jalur has strong potential to serve as a meaningful and contextual setting for physics learning by connecting fluid mechanics concepts with phenomena related to students' cultural and everyday experiences while simultaneously supporting the preservation of Indonesia's local wisdom.